1994
DOI: 10.1111/j.1937-5956.1994.tb00114.x
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Production Quantity Model With Learning and Forgetting Considerations

Abstract: The focus of this work is on the effects of learning on economic production quantity in batch production systems. We assumed that both unit variable manufacturing time and setup time follow a learning curve. We modified the classical Economic Production Quantity model to incorporate these two types of learning phenomena. We also incorporated the forgetting effect in our model so that a fraction of the learning is lost between consecutive lots. We developed a dynamic program to obtain the optimal solution to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Meanwhile, Jaber and Salameh (1995) propose optimal batch sizes based on Economic Production Quantity (EPQ) model by considering learning situation. Other researchers in the same field are Cheng (1991), Cheng (1994), Li and Cheng (1994), Chiu (1997), Chiu et al (2003), Chiu and Chen (2005), Chen et al (2008), Teyarachakul et al (2008), and Teyarachakul et al (2011). Although the researchers have found a method to determine the batch sizes, they have not considered on how to schedule the resulting batches on a machine.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Jaber and Salameh (1995) propose optimal batch sizes based on Economic Production Quantity (EPQ) model by considering learning situation. Other researchers in the same field are Cheng (1991), Cheng (1994), Li and Cheng (1994), Chiu (1997), Chiu et al (2003), Chiu and Chen (2005), Chen et al (2008), Teyarachakul et al (2008), and Teyarachakul et al (2011). Although the researchers have found a method to determine the batch sizes, they have not considered on how to schedule the resulting batches on a machine.…”
Section: Introductionmentioning
confidence: 99%
“…This is analogous to the learning concept in setup times (Chand 1989;Jaber and Bonney 2003;Li and Cheng 1994). Under this experience-based learning due to repetition, the duration and cost for the ith PM can be given as follows Teyarachakul 2009, 2013):…”
Section: The Modelmentioning
confidence: 98%
“…Therefore, researchers such as Ebert (1976), Cheng (1991), Salameh et al (1993), Li and Cheng (1994), Jaber and Guiffrida (2004), and Jaber and Bonney (2007) have used the following integral approximation to estimate the cumulative time for the first Q units of production: Camm et al (1987) showed that for a small value of b and a large value of Q, the approximation of Equation (8) (C) lie between 70% and 100% (Dutton and Thomas 1984, Smunt and Meredith 2000, Jaber and Bonney 2007 which yield a b value in the interval ranging from À0.515 to 0. Furthermore, the production quantity Q for each production cycle usually has a large scale.…”
Section: The Vendor's Total Costmentioning
confidence: 99%